Mikrosomia dan Usia Ibu Terhadap Kejadian Partus Lama Di Rumah Sakit Umum Daerah Prabumulih Tahun 2017 - Mela Paslentia (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2018)
Childbirth or long time partus is showed by the hazard phase more than 8 hours, childbirth had been running for 12 hours or more without baby born, and dilatasi cervical in the right of caution line to partograph. The object of this research is to know the correlation between macro Somnia and mother’s age with the occurrence of long time childbirth in the Local General Hospital of Prabumulih City Year 2017. This research used an analytic survey by using Cross Sectional approach. The population of this research was all mothers who gave birth in local General Hospital Of Prabumulih City Year 2017 with total numbers 1385 mothers. The number of samples in this research was 310 respondents. In univariate analysis known that 310 respondents taken that babies born who had diagnosis macro somnia were 80 respondents (25.8 %) and it was fewer those who born who didn't have macro somnia diagnosis were 230 respondents (74.2%). and mothers who had diagnosis risk age were 117 respondents (37.7%) it was fewer those who didn’t have risk age diagnosis were 193 respondents (62.3%). Bivariate analysis showed that macro somnia had a significant correlation with the occurrence of long time childbirth (p-value 0,000) and mother’s age had a significant correlation with the occurrence of long time childbirth (p-value 0,000). The Conclusion of this research is that: there is a significant correlation between macro Somnia and mother’s age with the occurrence long time childbirth in Local General Hospital Of Prabumulih City Year 2017.